Investigation on the interaction force measurement between bubble and particle in flotation based on resistance strain cantilever beam - Xibing REN; Lijuan SUN; Qinshan LIU; Yulong CHENG; Xiahui GUI; Yaowen XING (Meitan xuebao)
Flotation is an interfacial separation technique that achieves selective separation of valuable minerals from gangue based on differences in particle surface hydrophobicity. Its core functional unit is bubble- particle mineralization. The interaction force between bubble and particle directly determine the efficiency of bubble-particle mineralization and serve as a crucial window into the microscopic mechanism of flotation. However, high-precision and low-cost measurement of the force at the nano- and micro-scale has always been a significant challenge in this field. To address this, a new method for bubble-particle interaction force measurement based on resistance strain cantilever beam was proposed, which employs the principle of resistive strain to detect small deformation when force acting on an aluminum alloy cantilever beam. A Wheatstone bridge circuit was designed to complete the conversion, amplification, and output of resistance change into voltage signal. Subsequently, a self-constructed flotation micro-force testing system was developed, composed of resistance strain cantilever beam force sensor, displacement drive system, image acquisition system, signal amplification and acquisition system, control unit, and vibration isolation platform. The influence of particle surface hydrophobicity, bubble size, and bubble approach velocity on the interaction forces between bubble and particle was explored using the system. The results showed that the linear fitting adjusted R2 value of the calibration test result of the flotation micro-force testing system was 0.99989, exhibiting excellent linear response characteristic. The force sensitivity of the system was 72.57563 μN/mV, and the lower limit of actual force detection was about 2 μN. The adhesion force between bubble and particle showed a monotonic increasing trend with the increase of surfacecontact angle and bubble size. In the velocity range of 20-60 μm/s, the small gradient of bubble approaching velocity had little effect on the adhesion force. The experimental force measurements aligned closely with the theoretical predictions using the Young-Laplace equation. The flotation micro-force testing system offers simple and robust structure, high sensitivity, and cost-effective manufacturing, which promise broad applications in the basic research field of flotation interface interaction.